Interleukin-1α deficiency reduces adiposity, glucose intolerance and hepatic de-novo lipogenesis in diet-induced obese mice - Tal Almog; Michal Kandel Kfir; Hana Levkovich; Gadi Shlomai; Iris Barshack; Rinke Stienstra; Yaniv Lustig; Alicia Leikin Frenkel; Ayelet Harari; Yoram Bujanover; Roni Apte; Aviv Shaish; et al. (BMJ Open Diabetes Research & Care)
Objective While extensive research revealed that interleukin (IL)-1β contributes to insulin resistance (IR) development, the role of IL-1α in obesity and IR was scarcely studied. Using control, whole body IL-1α knockout (KO) or myeloid-cell-specific IL-1α-deficient mice, we tested the hypothesis that IL-1α deficiency would protect against high-fat diet (HFD)-induced obesity and its metabolic consequences.Research design and methods To induce obesity and IR, control and IL-1α KO mice were given either chow or HFD for 16 weeks. Glucose tolerance test was performed at 10 and 15 weeks, representing early and progressive stages of glucose intolerance, respectively. Liver and epididymal white adipose tissue (eWAT) samples were analyzed for general morphology and adipocyte size. Plasma levels of adiponectin, insulin, total cholesterol and triglyceride (TG), lipoprotein profile as well as hepatic lipids were analyzed. Expression of lipid and inflammation-related genes in liver and eWAT was analyzed. Primary mouse hepatocytes isolated from control mice were treated either with dimethyl sulfoxide (DMSO) (control) or 20 ng/mL recombinant IL-1α for 24 hours and subjected to gene expression analysis.Results Although total body weight gain was similar, IL-1α KO mice showed reduced adiposity and were completely protected from HFD-induced glucose intolerance. In addition, plasma total cholesterol and TG levels were lower and HFD-induced accumulation of liver TGs was completely inhibited in IL-1α KO compared with control mice. Expression of stearoyl-CoA desaturase1 (SCD1), fatty acid synthase (FASN), elongation of long-chain fatty acids family member 6 (ELOVL6), acetyl-CoA carboxylase (ACC), key enzymes that promote de-novo lipogenesis, was lower in livers of IL-1α KO mice. Treatment with recombinant IL-1α elevated the expression of ELOVL6 and FASN in mouse primary hepatocytes. Finally, mice with myeloid-cell-specific deletion of IL-1α did not show reduced adiposity and improved glucose tolerance.Conclusions We demonstrate a novel role of IL-1α in promoting adiposity, obesity-induced glucose intolerance and liver TG accumulation and suggest that IL-1α blockade could be used for treatment of obesity and its metabolic consequences.